The Islamic World in The Vortex of The Contemporary Israeli-Palestinian Conflict (2023-2024) - Wella Sherlita (Green Publisher Indonesia, 2025)
Since the Palestinian-Israeli conflict broke out in 1948, countless efforts at track one diplomacy have been intensively carried out by the leaders of Islamic countries, both in the UN General Assembly and the OIC forum, including by the Indonesian government. Islamic leaders have chosen to prioritize the principles of human intervention and dialogue in helping to resolve conflicts over the past 15 months. On the other hand, the awakening of civil society solidarity or public consciousness in various countries has emerged unexpectedly. Thousands of people took to the streets to hold peaceful demonstrations demanding a ceasefire, and recognition of Palestinian independence. The absence of coalition barbarslot forces to counteract the brutal Israeli military offensive was replaced by negotiations that led to a ceasefire agreement between Israel and Hamas on January 15, 2025 in Doha, Qatar. With a liberal approach, this article tries to outline the contribution of the Islamic world as well as the dilemmas faced when pioneering Hamas-Israel peace, using a qualitative descriptive method. The data were obtained from a combination of literature studies and interviews with a number of stakeholders.